Implementasi Cloud Storage Menggunakan OwnCloud yang High-Availability - Ikhwan Ar-Razy; Rinta Kridalukmana; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2016)
Implementation of practicum courses in Department of Computer Engineering Diponegoro University has some drawbacks, one of them is a lot of lab assistant and the practitioner experiencing difficulties in terms of archiving. One solution to solve the problem is implementing a shared file storage system that is easy and can be accessed by both practitioners or lab assistants. The purpose of this research is to build a cloud-based storage systems that are reliable to preventing crash damage hardware and high availability. The purpose of this research is achieved by designing the appropriate methodology. The result of this research is a storage system that is on the server side by using virtualization and data replication (DRBD) as a storage method. The system is composed of two physical servers and one virtual server. Physical servers are using Proxmox VE as operating system and virtual server is using Ubuntu Server as operating system. OwnCloud applications and files are stored in the virtual server. File storage system has several major functions, which are: upload, download, user management, remove, and restore. The functions are executed through web pages, desktop application and Android application.